Premarital Screening Uncovers Alarming Health Risks in Iraq: Pemeriksaan Pranikah Mengungkap Risiko Kesehatan yang Mengkhawatirkan di Irak - Qammar Shaker Hmood; Rawa Abdulkareem Abd; Riam Yousfe Muttair; Mohammed Jabbar Mohammed; Hayder Fadhil Okab (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Premarital screening programs, implemented globally since the 1970s, aim to improve reproductive health outcomes by identifying potential genetic and infectious risks before marriage. Specific Background: In July 2013, the Thi-Qar Governorate in Iraq introduced a premarital screening program to enhance health outcomes for pregnant women and their offspring. However, regional data on the efficacy and impact of such programs remain limited. Knowledge Gap: The prevalence and distribution of blood disorders and infectious diseases among couples in this region, and their implications for public health, have not been extensively documented. Aims: This study evaluates the pathophysiological status of couples undergoing premarital screening in Nasiriyah, Iraq, focusing on the prevalence of blood disorders and infectious diseases. Results: Data from 14,190 individuals (7095 couples) collected from January to December 2023 revealed significant health concerns: 34.40% had hemoglobin levels below 12 gm/dl, and notable percentages carried thalassemia and sickle cell anemia genes. Gender-specific analysis showed that all males tested positive for HIV, while significant proportions of females tested positive for HCV and T. palladium. No significant differences were found in the ABO blood system. Novelty: This study provides comprehensive, region-specific data on premarital screening outcomes in Iraq, highlighting significant disparities in disease prevalence between sexes and compared to other regions. Implications: The findings underscore the importance of enhancing premarital screening programs and integrating educational and preventive measures. Future research should include longitudinal studies to assess the long-term impact of these screenings and explore the benefits of incorporating genetic counseling to further mitigate hereditary and infectious risks. Highlights: High prevalence of blood disorders and infections in couples. Gender differences: all males positive for HIV, significant female infections. Need for improved education and prevention measures. Keywords: Premarital Screening, Hemoglobinopathies, Infectious Diseases, Nasiriyah, Iraq